Narrow-syntax and post-spellout movements: evidence from the syntax of idiomatic expressions in Arabic varieties - Rayyan, Mohammad; Jarrah, Marwan; Abusalim, Nimer (Heliyon, 2020)
This research paper investigates the syntax of idiomatic expressions consisting of the verb and the object/accompanying adjunct (VP idiomatic expressions, henceforth) in two Arabic varieties: Modern Standard Arabic (MSA) and Jordanian Arabic (JA). It shows that in order for VP idiomatic expressions to obtain their idiomatic reading, the predominate pattern of the word order in each variety (i.e., the VSO word order in MSA, but the SVO word order in JA) should be used; otherwise idiomaticity is not possible (with few exceptional cases discussed in the paper). We offer evidence that this restriction on the idiomaticity of VP idiomatic expressions in Arabic varieties follows from a proposed condition that the subject (even if it is not part of the idiomatic expression) and the verb (in addition to the object) should maintain a structurally local relation with each other in the narrow syntax, i.e. they should be included in the vP phase before the spell-out point. The paper shows that the movement of the verb to T0 in MSA and JA or lack thereof does not break idiomaticity, nor does the movement of the subject to Spec,TP in JA. These facts are taken as an indication that a distinction between narrow-syntax and post-spellout movements should be made. This provides evidence for proposals that distinguish between pre- and post-spellout movements (cf. Chomsky 2001, among others). Arts & humanities; Linguistics; Idiomatic expressions; Arabic varieties; Word order; PF movements; The architecture of language